Teknologi Pengolahan Limbah Industri Tahu sebagai Upaya Pengembangan Usaha Kecil Menengah (UKM) di Kecamatan Gambiran Kabupaten Banyuwangi - Sofi Faiqotul Hikmah; Abd. Rahman; Ilham Nur Kholiq; Zulfi Zumala Dwi Andriani (Jurnal Istiqro, 2019)
If waste is utilized properly, it will create new production and advance SMEs in Gambiran District so that it can minimize unemployment and increase the amount of income per capita of the community. This study has three objectives, namely: (1) To analyze the technology used in processing tofu industrial waste into nata de soya in Gambiran District, Banyuwangi Regency, (2) To analyze the technology used for processing tofu industrial waste into soy sauce in Gambiran District Banyuwangi, (3) To analyze the amount of production costs and costs of production sales from nata de soya and soy sauce products as an effort to develop Small and Medium Enterprises (UKM) in Gambiran District, Banyuwangi Regency. This research is classified into descriptive research with quantitative and qualitative types of data from the results of the experimental application to examine the act of making nata and soy sauce food products by the Gambiran District community by collecting data through surveys, observations, documentation, interviews and document analysis. In analyzing the document the results of the study will compare the feasibility of the two products obtained from whey to Nata de Soya and Ketchup products using the following feasibility analysis: TCI = FCI + WCI, TC = TFC + TVC, TR = P x Q, = TR – TC, dan BEP = . The analysis shows that the technology used in making nata de soya is biotechnology from the bacterium Acetobacter xylinum which has been fermented with sugar, vinegar and micin. While the technology of utilizing tofu industrial waste into soy sauce is one strategy to reduce environmental pollution. Experiments of making soy sauce are carried out by fermentation by methanogen bacteria from soaking solid waste and fermented with salt water bath after the tofu waste is dried until the moisture content reaches 12%. To analyze the production cost of making nata de soya with 3 liters of liquid waste is TCI = 16,500, TC = 16,500, TR = 25,500, Π = 9,000, BEP = 6 Liters. While for the analysis of the production cost of making soy sauce is TCI = 33,000, TC = 33,000, TR = 75,500, Π = 42,000, BEP = 2.2 Liter